Neurodydaktyczne aspekty procesu rozwiązywania testowego zadania matematycznego na podstawie badań eyetrackingowych - ROŻEK, Bożena; BŁASIAK, Władysław; ANDRZEJEWSKA, Magdalena; GODLEWSKA, Małgorzata; KOZUBOWSKI, Paweł; ROSIEK, Roman; SAJKA, Mirosława; STOLIŃSKA, Anna; WCISŁO, Dariusz (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
Contemporarily the necessity of regarding the knowledge of brain structureand functions in the didactic processes is more and more frequently discussed.Neurodidactics, as a cross-disciplinary science is engaged in the learning andeducation process which is based on the results of research on brain functioning.One of the non-invasive methods that can provide us with knowledge on brainfunctioning is the research carried out with an eye-tracker, a device used fortracing eyeball movements of a tested person. This paper will present a part ofthe research in which the eye-tracking technology has been used. The aim of thepresented research was an attempt to analyse the depth of information processingby a pupil during solving a mathematical test task. The research results point tocertain characteristic pupils’ behaviour while making decision concerning thechoice of an answer marked by them.